Pb evolution in the Martian mantle - Bellucci, J.; Nemchin, Alexander; Whitehouse, M.; Snape, J.; Bland, Phil; Benedix, Gretchen; Roszjar, J. (Elsevier BV, 2018)
© 2017 Elsevier B.V. The initial Pb compositions of one enriched shergottite, one intermediate shergottite, two depleted shergottites, and Nakhla have been measured by Secondary Ion Mass Spectrometry (SIMS). These values, in addition to data from previous studies using an identical analytical method performed on three enriched shergottites, ALH 84001, and Chassigny, are used to construct a unified and internally consistent model for the differentiation history of the Martian mantle and crystallization ages for Martian meteorites. The differentiation history of the shergottites and Nakhla/Chassigny are fundamentally different, which is in agreement with short-lived radiogenic isotope systematics. The initial Pb compositions of Nakhla/Chassigny are best explained by the late addition of a Pb-enriched component with a primitive, non-radiogenic composition. In contrast, the Pb isotopic compositions of the shergottite group indicate a relatively simple evolutionary history of the Martian mantle that can be modeled based on recent results from the Sm–Nd system. The shergottites have been linked to a single mantle differentiation event at 4504 Ma. Thus, the shergottite Pb isotopic model here reflects a two-stage history 1) pre-silicate differentiation (4504 Ma) and 2) post-silicate differentiation to the age of eruption (as determined by concordant radiogenic isochron ages). The μ-values ( 238 U/ 204 Pb) obtained for these two different stages of Pb growth are μ 1 of 1.8 and a range of μ 2 from 1.4–4.7, respectively. The μ 1 -value of 1.8 is in broad agreement with enstatite and ordinary chondrites and that proposed for proto Earth, suggesting this is the initial μ-value for inner Solar System bodies. When plotted against other source radiogenic isotopic variables (Sr i , γ 187 Os, ε 143 Nd, and ε 176 Hf), the second stage mantle evolution range in observed mantle μ-values display excellent linear correlations (r 2 > 0.85) and represent a spectrum of Martian mantle mixing-end members (depleted, intermediate, enriched).